Pengaruh Green Accounting, Circular Economy Practices, dan Eco-Innovation Terhadap Efektivitas Operasional Perusahaan Manufaktur Subsektor Barang Konsumsi di Bursa Efek Indonesia Periode 2020–2024. - Yuli Erlynda; Dwi Ermayanti Susilo (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
The increasing demand for sustainable business practices has encouraged manufacturing companies to begin incorporating environmental aspects into their operational processes. This study examines the relationship between the implementation of green accounting, circular economy practices, and eco-innovation and the operational effectiveness of manufacturing companies in the consumer goods subsector listed on the Indonesia Stock Exchange during the 2020–2024 period. The research employs a quantitative approach using panel data regression analysis. The data were obtained from companies’ annual reports and sustainability reports, with a sample of 26 firms resulting in 130 observations, selected through purposive sampling. The selection of the panel data regression model was conducted using the Chow test, Hausman test, and Lagrange Multiplier test, which indicated the Random Effect Model as the most appropriate estimation model. The results show that individually, green accounting, circular economy practices, and eco-innovation do not have a significant effect on companies’ operational effectiveness. Nevertheless, green accounting and eco-innovation exhibit a positive relationship tendency, while circular economy practices show a negative relationship. These findings indicate that the implementation of sustainability aspects in consumer goods companies remains partial and has not yet been fully integrated into core operational systems. The results of this study are expected to serve as a basis for corporate evaluation in formulating sustainability strategies and as a reference for future research development.